Enotirni sistem upravljanja v Evropski uniji, Veliki Britaniji in Sloveniji - Frešer, Petra (Podjetje in delo, 2018)
The paper analyses and compares the legal regulation of the one-tier corporate governance system in Slovenia, Great Britain and the European Union. The regulation of the one-tier management system is outlined in the Slovenian Companies Act, the British Companies Act 2006 and the Council Regulation (EC) on the Statute of a European Company (SE). The author presents in detail the findings of Slovenian and British theories, and presents the European system and its influence on the legal regulation of the one-tier system in Slovenia and Great Britain. The common characteristics of the differences between the two national systems and the management system set at European Union level are also presented.
Keywords: board of directors; Companies Act; corporate governance; Council Regulation 2157/2001; delniške družbe; direktorji; executive directors, non-executive directors; gospodarsko pravo; korporativno upravljanje; one-tier system; pravna ureditev; primerjalno pravo; upravni odbor